Ч. 1; Практические занятия по физике на основе применения информационных технологий - Ерофеева Г. В. Галина Васильевна; Крючков Ю. Ю. Юрий Юрьевич; Склярова Е. А. Елена Александровна; Чернов И. П. Иван Петрович (2009, 2009)
Заглавие с титульного экрана